Former Yugoslav Republic of Macedonia : Request for Stand-By Arrangement and Extension of Repurchase Expectations. (IMF Staff Country Reports; Country Report ;, 2005)
This paper discusses the Former Yugoslav Republic of Macedonia's (FYR Macedonia) Request for a Stand-By Arrangement and Extension of Repurchase Expectations. The authorities have asked the IMF to support an ambitious program that includes structural reforms that address the root causes of FYR Macedonia's weak performance. On the macroeconomic front, the near-term aims of the program are to strengthen the exchange rate peg by increasing foreign exchange reserves and to manage the transition from official budget financing to market-based financing. The program also aims to secure medium-term fiscal sustainability.